The Effects of Group Therapeutic Singing on Cortisol and Motor Symptoms in Persons With Parkinson's Disease - Stegemöller, Elizabeth L.; Zaman, Andrew; Shelley, Mack; Patel, Bhavana; Kouzi, Ahmad El; Shirtcliff, Elizabeth A. (Frontiers in Human Neuroscience, 2021)
The inclusion of music into the treatment plan for persons with Parkinson’s disease (PD) may be a viable strategy to target multiple motor symptoms. However, potential mechanisms to explain why music has an impact on multiple motor symptoms in persons with PD remain understudied. The purpose of this study was to examine the acute effects of one hour of group therapeutic singing (GTS) on physiological measures of stress and clinical motor symptoms in persons with PD. We posit that improvement in motor symptoms after GTS may be related to stress reduction. Seventeen participants with PD completed one hour of GTS and eight participants completed one hour of a quiet reading (control session). Cortisol was collected via passive drool immediately before and after the singing and control session. The Unified Parkinson’s Disease Rating Scale (UPDRS) Part-III (motor examination) was also video-recorded immediately before and after the singing and control session and scored by two raters masked to time and condition. Secondary outcome measures for quality of life, depression, and mood were collected. Results revealed no significant change in cortisol or motor UPDRS scores, as well as no significant relationship between cortisol and motor UPDRS scores. There was a trend for the singing group to report feeling less sad compared to the control group after the one-hour session (effect size = 0.86), and heart rate increased in the singing group while heart rate decreased in the control group after the one-hour session. These results suggest that an acute session of GTS is not unduly stressful and promotes the use of GTS for persons with PD. Multiple mechanisms may underlie the benefits of GTS for persons with PD. Further exploring potential mechanisms by which singing improves motor symptoms in persons with PD will provide greater insight on the therapeutic use of music for persons with PD.